-42-2x=6-6x

Simple and best practice solution for -42-2x=6-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -42-2x=6-6x equation:


Simplifying
-42 + -2x = 6 + -6x

Solving
-42 + -2x = 6 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-42 + -2x + 6x = 6 + -6x + 6x

Combine like terms: -2x + 6x = 4x
-42 + 4x = 6 + -6x + 6x

Combine like terms: -6x + 6x = 0
-42 + 4x = 6 + 0
-42 + 4x = 6

Add '42' to each side of the equation.
-42 + 42 + 4x = 6 + 42

Combine like terms: -42 + 42 = 0
0 + 4x = 6 + 42
4x = 6 + 42

Combine like terms: 6 + 42 = 48
4x = 48

Divide each side by '4'.
x = 12

Simplifying
x = 12

See similar equations:

| 7-9x=7x+18 | | (7x^3+4x)(x^2+2)= | | 4(x-3)=23-x | | 9(2+x)=63 | | 4x+13=94 | | 2(3-5+7)+6= | | 5(14-x)=60 | | 8(x+1)=48 | | 3x(3+5)=24 | | -32=4(x+3) | | (2x+4y)+(4x+7y)=180 | | -3x^2+21x=15 | | 5x+5+4x+5+35=180 | | 1=-.5(3k-4) | | 3.50x=84 | | (3+3.50)x=84 | | 5m^2+2=47 | | -2/3q+2q=6/5q+12/5 | | 2[(12+2x)+(15+2x)]=74 | | 8y^2-23y-3= | | (-762.46)=h-32.061 | | 4x-12=72 | | x^2-12x-14=41 | | 21.21+p=(-101.6) | | (3u+7)(8+u)=0 | | cos(3x)=cos(x) | | 17x^2-153=0 | | 11/20+5/20 | | 102.8=g(-66.09) | | b-17.8=(-36) | | x^2-5x=12-4x | | 7/8x-1/4+3/8x=1/16x |

Equations solver categories